The First Settlements and their Impaces on the First Nations in North America - Baráthné Gebefügi, Ildikó (2008)
The aim of this thesis to present how these elements influenced the life of the Aboriginal pepoles. The structure of the thesis focuses on the period from 1000 AD, when the Viking reached the North American shores, up to Confederation. The region I concentrated on was, mainly the St. Lawrence Valley, the Great Lakes,and the Hudson Bay with Rupert’s Land. angol nyelv és irodalom szakos tanár (kiegészítő levelező képzés) egyetemi